(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, we will talk about the production of the product input costs and their types, rational and efficient use of available resources in production, as well as some important issues that affect the cost of the product passed. In addition, scientific proposals and practical recommendations have been developed to reduce the cost of manufactured products using modern innovative methods in product cost calculation.